FLEXITANKS IN BAG-IN-BOX TRANSPORTATION TECHNOLOGY: TERM REVISION BASED ON FUNCTIONAL ROLE - Drozhzhyn, O. L.; Berestenko, V. V. (Systems and Technologies, 2026)
This article is devoted to researching the place and functional role of flexitanks (FT) in bag-in-box (BIB) container trans- port technology. The relevance of this work is due to the growing share of containerization in the global transport market and the active search for more flexible and economical solutions for the delivery of liquid cargo. The development of FT as an alternative to traditional tank containers in the 1970s opened up new opportunities for the logistics of food products, chemicals, and other safe liquids, but at the same time raised a number of questions regarding the legal definition of their status. In particular, there is no clear interpretation in international practice as to whether FTs should be classified as packaging materials or considered as supplementary container equipment. The purpose of the study is to clarify the term “flexitank” based on its functional purpose, as well as to analyze the conse- quences of classifying this category under the terms ‘packaging’ or “container equipment” in insurance and customs clearance practices. The basis for the study was the definition of the elements of BIB technology from international standards and conven- tions, as well as practical case studies of legal cases. The article describes in detail the technological aspects of the BIB system and proves the functional dependence of FT on container equipment, which makes it impossible to use it as an independent transport tank. Through analysis of legal norms and court decisions, it has been proven that FTs cannot be considered packag- ing, since they require a container to perform their role and are therefore auxiliary equipment. The scientific novelty lies in the proposal of a clear terminological distinction: defining FT as an elastic tank that is installed in a universal cargo container and acts as additional equipment. This approach allows for the removal of a number of contradictions in the field of insurance and customs clearance, and also provides a basis for a clear distinction between the rights and obligations of participants in inter- modal transport. The results of the study are of practical importance for intermodal, freight forwarding, shipping, and insurance companies, carriers, and cargo owners, as they enable the optimization of contractual relationships, reduce the risk of litigation, and ensure transparency in intermodal bulk cargo transportation procedures. The practice recommendations in the conclusions are meant to make bulk cargo transportation safer and more efficient, as well as to standardize transportation terminology.